Faktor-faktor yang mempengaruhi keberkesanan pengurusan keselamatan dan kesihatan pekerjaan di CMS Steel Berhad - Noraina, Md Idrus (Universiti Malaysia Sarawak, (UNIMAS), 2005)
The aim of this reseach was to identify the factors that influence the effectiveness of occupational safety and health at CMS Steel Berhad such as safety policy, safety training, safety program. strategic management, employers' responsibilities and employees 'responsibilities. 33 persons were selected as respondents. A few sets of questionaires were distributed as a form of data collection. The reseach found that the effectiveness level of occupational safety and health management at CMS Steel Berhad was high (90.9%). From the Pearson correlation analysis, the fmdtngs revealed the significant levels for each actors. ' The Linear Regression analysis indicated that the dominan factor of this reseach was the safety program (R' _ 0.227). Overall, the result illustrated that the organization should give an emphasis on certain safety aspect to improve the occupational safety and health management system in the compan